Hyperbaric Oxygen Therapy in Branch Retinal Artery Occlusion in a 15-Year-Old Boy with Methylenetetrahydrofolate Reductase Mutation - Ali Riza Cenk Celebi; Sibel Kadayifcilar; Bora Eldem (Case Reports in Ophthalmological Medicine)
Purpose. To report the efficacy of hyperbaric oxygen (HBO) therapy in a case of branch retinal artery occlusion (BRAO) in a 15-year-old boy. Methods. We report a 15-year-old boy with sudden loss of vision due to BRAO. Examination included laboratory evaluation for systemic risk factors. Follow-up exams included visual acuity, fundus examination, fundus fluorescein angiography, and visual field testing. HBO therapy was employed for treatment. Results. Medical history was positive for isolated glucocorticoid deficiency. Laboratory evaluation disclosed hyperhomocysteinemia and methylenetetrahydrofolate reductase (MTHFR) mutation. The visual acuity 0.05 at presentation improved to 0.8 after 20 days of HBO therapy. There was no change on visual fields. Conclusion. In this pediatric case, HBO therapy was useful in the treatment of BRAO.